The Role of E-WOM Credibility and Online Engagement in Shaping Online Purchase Intention: An Empirical Study - Tri Andari Ratna Widyastuti; Audra Fahrezy Putra (Majalah Ilmiah Bijak, 2025)
This study aims to analyze the influence of electronic word of mouth (eWOM) credibility and online engagement intentions on online purchase intentions among e-commerce consumers in Indonesia. This study uses a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis techniques. Respondents totaled 198 people who were selected purposively, with the criteria of active social media users and having made e-commerce transactions in the last three months. The results show that eWOM credibility and online engagement intentions have a positive and significant effect on online purchase intentions. This research contributes to the development of digital marketing strategies and enriches the literature on consumer behavior in the digital context.